1994
DOI: 10.1002/hep.1840190114
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic and metabolic changes in fulminant hepatic failure: A retrospective study

Abstract: The purpose of this retrospective study was to determine cerebral hemodynamic and metabolic changes in comatose patients with fulminant hepatic failure. Computerized tomography of the brain and cerebral blood flow measurements by the xenon-computerized tomography scan or intravenous xenon-133 methods were obtained in 33 patients with fulminant hepatic failure. In a subgroup of 22 patients, arteriojugular venous oxygen content difference and cerebral metabolic rate for oxygen were determined. Carbon dioxide rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(58 citation statements)
references
References 35 publications
(5 reference statements)
1
54
0
3
Order By: Relevance
“…It has been shown that increasing inflammation has a direct correlation with increasing CBF 64 which in turn is known to raise intracranial pressure. 65 This has been further demonstrated by studies which have examined therapeutic strategies that reduce systemic inflammation and cerebral hyperemia.…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Acutementioning
confidence: 96%
“…It has been shown that increasing inflammation has a direct correlation with increasing CBF 64 which in turn is known to raise intracranial pressure. 65 This has been further demonstrated by studies which have examined therapeutic strategies that reduce systemic inflammation and cerebral hyperemia.…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Acutementioning
confidence: 96%
“…2 Traditionally, cerebral perfusion in critically ill patients has been indirectly evaluated by measure of cerebral perfusion pressure (MAP minus intracranial pressure) or by internal jugular venous oxygen content, where a constant cerebral oxygen consumption is assumed. 3 Obviously, these invasive measures do not provide sufficient insight in cerebrovascular hemodynamics. Repeated measurements every day of CBF by, for example, I33 Xe technique is a cumbersome and a measured in the right middle cerebral artery by a 2-MHz probe, and blood samples were drawn at intervals of 5 mm Hg.…”
mentioning
confidence: 99%
“…Loss of cerebrovascular autoregulation and development of cerebral hyperemia, described in patients with advanced ALF [111], [112], [113], [114] and [115], are relevant to the pathogenesis of brain edema and intracranial hypertension [116]. Loss of cerebrovascular autoregulation may cause luxury perfusion or hypoxia during increases or decreases of systemic arterial pressure, respectively.…”
Section: Cerebrovascular Haemodynamicsmentioning
confidence: 99%
“…Loss of cerebrovascular autoregulation may cause luxury perfusion or hypoxia during increases or decreases of systemic arterial pressure, respectively. Cerebral hyperemia is associated with brain edema and mortality in ALF [113] and [117]. The mechanisms by which cerebral hyperemia enhances brain edema and ICP in ALF have been reviewed by Larsen and Wendon [116].…”
Section: Cerebrovascular Haemodynamicsmentioning
confidence: 99%